SEJARAH AGAMA ISLAM DAN PERKEMBANGANNYA - Azhima, Muhammad Fauzan (UIN Sumatera Utara Medan, 2023)
To discuss a religion, one of which is Islam which starts from the geographical aspect of the spread of religions in the world. Then, it can also be understood with the emergence of Islam into this world as one of the best religions in the world, especially those born in the Middle East world, namely Judaism, Christianity, and Islam. These three religions are known as religions that come from revelation or the sky. With the next stage, it can be understood about the process of the development of Islam which is one of the religions that is widely embraced by the general public in this world. the words included. The object of this research is analyzed how the history of the Islamic religion is. This article is compiled based on data and references obtained from books and scientific journals related to the discussion. This writing method is a literature study and the data that has been collected is arranged and sorted logically and systematically Religion is something you need to know about the meaning it contains, and because religion is based on the psychological nature of belief, its strength or weakness depends on how it is embedded in the soul, it's different. Therefore, by knowing the meaning contained in a religion, someone who is religious can feel the goodness and tranquility that comes from the teachings of that religion. Westerners tend to see religion as a phenomenon that manifests itself in religious adherents. This is because they have long developed a way of seeing things just as they are, or only appearing in the eyes of human social life. Islam which was revealed in the Arabian Peninsula has brought the Arabs who were originally backward, ignorant, unknown and ignored by other nations, into a developed and civilized nation. He is very fast moving to develop the world, fostering a culture and civilization that is very important in human history until now. Islam is different from other religions. Islam is not culture, but creates culture. The resulting culture is called Islamic culture or civilization. The foundation of